Cortical contributions to anticipatory postural adjustments in the trunk. (25th February 2018) - Chiou, Shin‐Yi; Hurry, Madeleine; Reed, Thomas; Quek, Jing Xiao; Strutton, Paul H.
Abstract : Key points: Increases in activity of trunk muscles that occur prior to, or concurrent with, a voluntary limb movement are termed anticipatory postural adjustments (APAs). APAs are important for maintaining postural stability in response to perturbations but the neural mechanisms underlying APAs remain unclear. Our results showed that corticospinal excitability of erector spinae (ES) muscle increased at 40 ms prior to rapid shoulder flexion, with a reduction in intracortical inhibition and no change in spinal excitability. Changes in corticospinal excitability were observed in ES, with similar excitability profiles between standing and lying positions, but were not observed in rectus abdominis. We suggest that the neural control of postural adjustments involves changes at a cortical level, which in part are due to reduced inhibition. Abstract: Voluntary limb movements are associated with increases in trunk muscle activity, some of which occur within a time window considered too fast to be induced by sensory feedback; these increases are termed anticipatory postural adjustments (APAs). Although it is known that the function of APAs is to maintain postural stability in response to perturbations, excitability of the corticospinal projections to the trunk muscles during the APAs remains unclear. Thirty‐four healthy subjects performed rapid shoulder flexion in response to a visual cue in standing and lying positions. Transcranial magnetic stimulation (TMS) was delivered over the trunk motor cortex to examine motor evoked potentials (MEPs) in erector spinae (ES) and in rectus abdominis (RA) muscles at several time points prior to the rise in electromyographic activity (EMG) of anterior deltoid (AD) muscle. TMS was also used to assess short‐interval intracortical inhibition (SICI) and cervicomedullary MEPs (CMEPs) in ES in the standing position. MEPs in ES were larger at time points closer to the rise in AD EMG in both standing and lying positions, whereas MEPs in RA did not differ over the time course examined. Notably, SICI was reduced at time points closer to the rise in AD EMG, with no change in CMEPs. Our results demonstrate that increasing excitability of corticospinal projections to the trunk muscles prior to a voluntary limb movement is likely to be cortical in origin and is muscle specific. Key points: Increases in activity of trunk muscles that occur prior to, or concurrent with, a voluntary limb movement are termed anticipatory postural adjustments (APAs). APAs are important for maintaining postural stability in response to perturbations but the neural mechanisms underlying APAs remain unclear. Our results showed that corticospinal excitability of erector spinae (ES) muscle increased at 40 ms prior to rapid shoulder flexion, with a reduction in intracortical inhibition and no change in spinal excitability. Changes in corticospinal excitability were observed in ES, with similar excitability profiles between standing and lying positions, but were not observed in rectus abdominis. We suggest that the neural control of postural adjustments involves changes at a cortical level, which in part are due to reduced inhibition.